Scary story - "Cowley, Joy" (Hawthorn; Mimosa McGraw-Hill, 2007)
Ross Beansack, the big hairy author, has been asked by young readers to write a story about ghosts. The very modern publisher is horrified when she hears of his plans. "We don't do ghosts," she says. "Go back home and save the rainforest." Ross Beansack sets off to do his own research in the local haunted house ..
Donated by "Book Planet", Dated 18-4-2025.
Keywords: ghost stories